Classroom Management in Creating Effective Learning in MIS Al-Ashriyah Banjarmasin - Rahmawati, Laili; Sholeh, Makherus (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to describe classroom management in creating effective learning including the planning of classroom management, the implementation of classroom management, and the supervision of classroom management at MIS Al-Ashriyah. The method used in this research is descriptive qualitative, data collection using observation and interviews. The results of this study indicate that planning of classroom management is carried out by making learning implementation plans, preparing the necessary learning media, and always establishing good communication with parents and guardians of students. The implementation of management is carried out with the expertise of the teacher in the classroom, starting from the attitude of the teacher who is calm, friendly, and smiling, always greeting and greeting when entering the class. At the beginning of each lesson, always pray together and recite the Qur'an which is led directly by the teacher, then the teacher makes the class atmosphere comfortable and safe, followed by student arrangements starting from checking student attendance lists, picket class cleanliness, as well as assessing and appreciating students. Learning support facilities are also provided, such as a reading corner, the provision of plastic folders used to store a collection of assignments and grades, and a drawer where learning tools are stored, managing the implementation of learning by compiling based on student circumstances, delivering easy-to-understand material, while supervision is carried out by class teachers and principals which is carried out continuously or continuously.